European Conference and Exhibition on Optical Communication 2012
DOI: 10.1364/eceoc.2012.we.2.b.2
|View full text |Cite
|
Sign up to set email alerts
|

Simple Intradyne PSK System for udWDM-PON

Abstract: A homodyne coherent receiver for ultra-dense WDM-PON with off the shelf components is presented. It consists of a conventional DFB, phase switched clock signal, an optical coupler instead of a 90º hybrid, balanced photodetectors and digital signal processing. The phase swing for a DBPSK signal was optimized and the performance was experimentally evaluated in terms of the sensitivity for several laser linewidths. The acceptable frequency offset and clock time delay was also assessed. The results exhibit a sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…3, a), an ASK or PSK modulation is obtained with a Mach-Zehnder (MZ) modulator controlled by the input data at 1.25 Gb/s bit rate [20]. The detection is enabled by an optical hybrid, which can be 90º or 120º, and 3 or 4 PIN photodiodes with integrated transimpedance amplifier (TIA).…”
Section: A Onu Architecturesmentioning
confidence: 99%
See 2 more Smart Citations
“…3, a), an ASK or PSK modulation is obtained with a Mach-Zehnder (MZ) modulator controlled by the input data at 1.25 Gb/s bit rate [20]. The detection is enabled by an optical hybrid, which can be 90º or 120º, and 3 or 4 PIN photodiodes with integrated transimpedance amplifier (TIA).…”
Section: A Onu Architecturesmentioning
confidence: 99%
“…When using coherent homodyne detection, the channel spacing is taken to be 6.25 GHz [20], [22], and the required bands can be allocated in the C-band and/or in the L-band. Although the minimum wavelength separation between two adjacent channels is only 3 GHz [20]; considering the guard bands, the wavelengths drifts, the nonlinearities constrains, and future ITU grid, 6.25 GHz are used. The laser tunability is assumed to be 0.1 nm/ºC, with a range of +/-10ºC (+/-1 nm or +/-20 channels in C-band), which can be achieved with a Peltier or just by heating the TL by +10ºC and, afterwards, incrementing or decrementing its temperature up to 10ºC.…”
Section: B Wavelength Channel Assignment In Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…8(a). The electrical signal at the output of the photodiodes after amplifying is sampled with a 50 GSa/s real-time oscilloscope at 12.5 GSa/s with 10, 5, 4 samples per bit, respectively [12]. The intermediate frequency is selected at twice the bit rate.…”
Section: Gy Chu Et Al / Optics Communications ∎ (∎∎∎∎) ∎∎∎-∎∎∎mentioning
confidence: 99%
“…Coherent detection has been confirmed that it can improve the sensitivity and the spectrum efficiency in access network [12,13]. Compared with homodyne detection, heterodyne detection presents inherent image frequency interference, and as a result homodyne/intradyne reception is considered a better solution [14].…”
Section: Introductionmentioning
confidence: 99%